2003
DOI: 10.1002/hlca.200390269
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Characterisation, and Reactivity of Some Polydentate Phosphinoamine Ligands with Benzene‐1,3‐diyl and Pyridine‐2,6‐diyl Backbones

Abstract: 2 affords the corresponding tetrasulfide or tetraselenide, respectively, in good yield. The complexes [1,3-{Mo(CO) 4 (Ph 2 P) 2 N} 2 (C 6 H 4 )] and [2,6-{Mo(CO) 4 (Ph 2 P) 2 N} 2 (C 5 H 3 N)] were prepared from the reaction of these phosphinoamines with [Mo(CO) 4 (nbd)] (nbd norbornadiene) in toluene, and the structure of the latter complex has been determined by single-crystal X-ray diffraction analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…The ligands 2,6-{(Ph 2 P) 2 N} 2 C 5 H 3 N (L 1 ) [21] and 2,6-{(Ph 2 P)HN} 2 C 5 H 3 N (L 3 ) [19] and the complex Au(tht)Cl (tht ϭ tetrahydrothiophene) [22] were prepared according to literature methods. Solvents were dried using appropriate reagents and distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The ligands 2,6-{(Ph 2 P) 2 N} 2 C 5 H 3 N (L 1 ) [21] and 2,6-{(Ph 2 P)HN} 2 C 5 H 3 N (L 3 ) [19] and the complex Au(tht)Cl (tht ϭ tetrahydrothiophene) [22] were prepared according to literature methods. Solvents were dried using appropriate reagents and distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that CH 2 Cl 2 is a more appropriate solvent. 30 Therefore we chose CH 2 Cl 2 as the solvent in this synthesis process. In a typical reaction, 2 equivalents of Ph 2 PCl were added slowly to a CH 2 Cl 2 solution of p-methoxyaniline containing 2.2 equivalents of Et 3 N to afford the bidentate diphosphinoamine ligand Ph 2 PN(p-C 6 H 4 OMe)PPh 2 .…”
Section: Syntheses Of Ligand and Nickel (Ii) Complexmentioning
confidence: 99%
“…Polydentate aminophosphine ligands with more than one N(PR 2 ) 2 unit have also been reported [6,7]. In general, bis(phosphino)amines with P-N-P skeletons have proved to be versatile ligands [8].…”
Section: Introductionmentioning
confidence: 99%